Pembelajaran Pendidikan Agama Islam (PAI) Model Keberagamaan Inklusif untuk Mencegah Radikalisme Beragama Dikalangan Siswa SMA - Abdurrohman Abdurrohman; Huldiya Syamsiar (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2017)
The phenomenon of religious radicalism has become a global threat of the 21st century that phenomenon was a result of Islam as anaccused religion and was often associated with a terrorist religion. Educational institutions often